BIOACTIVITY OF CINNAMON (Cinamomum sp) - Tafzi, Fitri (Indonesian Food Science and Technology Journal, 2020)
Abstract-Cinnamon has been widely used as a spice in food and medicine. Cinnamon grow in the Asian region. Indonesia is one of the cinnamon producing countries. The chemical composition of cinnamon plants varies according to the variety, the part of the plant, the place and the climate to grow. The main bioactive component in cinnamon bark is cynnamaldehide. Cynnamaldehide in cinnamon has good physiological effects on body health such as antioxidants, anticancer, anti-inflammatory, antidiabetic, antidyslipidemicanti-hyperuricemia, and antimicrobial properties. Research is generally still conducted in vitro, clinical trial limited. Keywords— cinnamon; antioxidant; anticancer; cynnamaldehyde.